RESEARCH WORK AT HIGHER MEDICAL INSTITUTIONS IN SIBERIA AT THE END OF THE 50s – THE BEGINNING OF THE 90s OF THE XXTH CENTURY - V. V. PETRIK (Высшее образование в России)
The article analyzes the activity of Siberian medical higher education institutions in the development of the research areas in the late 50’s – early 90’s XX century. The paper explores the most significant achievements of medical scientists of the region in the leading fields of medical science: therapy, surgery, pediatrics, obstetrics and gynecology, dentistry, genetics, microbiology and other areas. It is shown that the most significant volume of research was carried out in Tomsk, Irkutsk, Novosibirsk and Omsk medical institutes where there were formed the authoritative scientific schools. The teachers and researchers of medical institutes actively participated in the implementation of regional programs including the program “Human Health in Siberia”, which was a part of the superprogram “Siberia”. The author dwells on the experience of establishing business ties in conducting research, using of experimental and clinical base between university and academic medical science. Forms and methods of interaction in this field of scientific activity, such as scientific and practical associations, interdepartmental laboratories, creative contracts and agreements, participation of scientists in the work of elected academic and higher educational institutions are analyzed. The author affirms that along with the strengthening of business contacts between university and academic medical institutions, there were many difficulties: communications were often spontaneous, a great deal depended on the relationship between the governing structures of medical institutions and academic research institutes, there was a disunity in solving some scientific issues. The obtained data allow to draw a conclusion that the research work of medical universities in Siberia in the period under review was aimed at increasing the scale of research, the growth of scientific potential and raising the its effectiveness in the interests of socio-economic development of the region and the country as a whole. The work is based on archival sources and materials, which are for the first time are being introduced into scientific circulation.